A web based cross-platform application for teleconsultation in radiology - Kammerer, Ferdinand J.; Hammon, Matthias; Schlechtweg, Philipp; Uder, Michael; Schwab, Siegfried (Journal of Telemedicine and Telecare, 2015)
The growing complexity of radiologic examinations and interventional procedures requires frequent exchange of knowledge. Consequently a simple way to share and discuss patient images between radiology experts and with colleagues from other medical disciplines is needed. Aims of this work were the development and initial performance evaluation of a fast and user friendly, platform independent teleconsultation system for medical imaging. A local back end system receives DICOM images and generates anonymized JPEG files that are uploaded to an internet webserver. The front end running on that webserver comprises an image viewer with a specially developed pointer element for indicating findings to collaborative partners. The front end that uses only standard web technologies works on a variety of different platforms, mobile devices and desktop computers. Images can be accessed by simply calling up a special internet address in a web browser that may be exchanged between users (e.g. via email). A speed evaluation of the system showed good results: For example the preparation and upload of a standard head CT took less than 21 seconds. The data volume of the same series and the viewer application could be transferred to a mobile phone in less than 42 seconds via a UMTS network or in less than 3 seconds via a HSPA network. The presented system with its minimal hard- and software requirements, its simplicity and platform independence might be a promising tool in the increasingly important area of teleconsultation.
EVALuna2:14496